Analysis of the written curriculum, actual curriculum, and hidden curriculum and their integration into education and teaching - Malik Simanullang; Fauzan; Bobi Erno Rusadi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Abstract: This study aims to analyze various forms of curriculum related to Islamic religious education through a comprehensive approach, including the written curriculum, actual curriculum, and hidden curriculum. Then this research also analyzes how the three forms of curriculum are integrated into the learning process so that they can achieve learning objectives. This approach is very important in understanding how the curriculum is formally designed, actually implemented in the field, and then the unofficial values that participate in shaping students learning experiences. Because we have observed in many schools that many educators still do not understand the division of curriculum forms, so they are confused about their implementation in the field. This study not only describes the forms of curriculum textually, but in this study the author attempts to explain the forms of curriculum contextually so that readers can delve deeper into the forms of curriculum. The method used is descriptive qualitative literature study or library research, and analyzing journal documentation, articles related to the discussion. The results of this study indicate that the written curriculum, actual curriculum, and hidden curriculum must be integrated with each other for maximum learning achievement, so that both students and teachers can easily carry out the learning process. Therefore, this study explains that the written curriculum is the formal curriculum, and the actual curriculum is the implementation of the formal curriculum, and the hidden curriculum is a supporting aspect that is not explicit, but has an influence the shape of student character. Hopefully, this research is expected to contribute so that we can see the development of an effective and relevant curriculum according to the needs of students. Therefore, academics and aducational staff can maximize the implementation of the curriculum comprehensively.